Text analytics APIs, Part 1: The bigger players. (14th February 2018) - DALE, ROBERT
Abstract: If you're in the market for an off-the-shelf text analytics API, you have a lot of options. You can choose to go with a major player in the software world, for whom each AI-related service is just another entry in their vast catalogues of tools, or you can go for a smaller provider that focusses on text analytics as their core business. In this first of two related posts, we look at what the most prominent software giants have to offer today.